Characteristics of ethical and unethical leadership: Exploratory findings from post-Soviet Kazakhstan - Lewis, Jason (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This research investigates the perceptions of ethical and unethical leadership within Kazakhstani business organizations, aiming to discern how individuals in Kazakhstan conceptualize and enact ethical and unethical leadership. Employing a qualitative research paradigm with a constructivist perspective, data were gathered through semi-structured interviews with 23 participants in Kazakhstan. Inductive, grounded theory methods of analysis were utilized to analyze the interview data. The study identified nine characteristics of ethical leadership perceived by participants, along with five characteristics of unethical leadership. While the sample size and geographic focus of the study limit the generalizability of findings, the findings provide valuable contributions to understanding ethical leadership in non-Western contexts, offering implications for leadership development and organizational practices within Kazakhstan. This study fills a gap in the literature regarding the perception and practice of ethical leadership in Kazakhstan, shedding light on cultural nuances and ethical values that shape leadership behaviors in the region.